HPV vaccination campaigns in Ethiopia and Bangladesh: Strategic implementation, challenges, identifying best practices and lessons for success in low and middle-income countries - Abu Sadat Mohammad Sayem; Brian Atuhaire; Anisur Rahman Siddique; Riad Mahmud; Melkamu Ayalew Kokebie; Godfrey Musuka (Vaccine: X)
Cervical cancer is the fourth most common cancer in women globally, with around 660,000 new cases and 350,000 deaths in 2022, primarily in low- and middle-income countries. Vaccination at ages 9–14 is a highly effective way to prevent HPV infection and related cancers. Significant advancements have been achieved in the development and effectiveness of HPV vaccines, accompanied by a notable increase in global vaccination initiatives. Numerous countries have gained valuable insights from implementing HPV vaccination programs targeting adolescent girls through pilot initiatives, demonstration projects, and extensive nationwide campaigns. Over 140 countries have introduced HPV vaccines across the globe. This study examines implementation challenges in Bangladesh and Ethiopia despite high vaccination coverage. It also aims to gather best practices from recent campaigns and include respondents' suggestions.This study employs a qualitative approach to examine the HPV campaigns implemented in two countries in 2023. The research involved collecting data through interviews conducted with 20 key informants, ranging from national to sub-district levels in 2024. Informed consent was obtained from all participants prior to the interviews. Narrative analytical methods were utilized to analyze the collected data.The findings indicate that both countries face distinct challenges despite the recommendations for implemented strategies from the WHO, which were adopted in the respective country context.The effectiveness of school-based, facility-based (Immunization fixed center), and community outreach-based approaches is significantly influenced by health communication strategies, operational modalities, and various contextual factors. Several best practices, including integration, partnership, digitization, e-microplanning, and the engagement of religious leaders and teachers, played a crucial role in enhancing coverage. The study presented specific recommendations, such as incentivizing health workers, optimizing operational modalities during campaigns, and reinforcing planning efforts to reach vulnerable populations. This document summarizes the status, implementation strategies, challenges, and exemplary practices concerning HPV vaccination campaigns in the two countries under consideration.In conclusion, there are opportunities to refine the current strategy by customizing interventions to achieve optimal coverage. The lessons learned from this experience can be effectively applied in similar contexts and in countries that are set to launch HPV campaigns in the coming years.